The Dahl’s Model for the Inelastic Bending Behavior of Textile Composite Preforms. Analysis of its Influence in Draping Simulation - Ghafour, Théo A.; Colmars, Julien; Boisse, Philippe (Frontiers in Materials, 2021)
Most of the numerical simulations of dry textile reinforcements forming are based on a macroscopic approach and continuous material models whose behavior is assumed to be elastic (linear or nonlinear). On the one hand, the experience shows that under loading/unloading stresses, residual inelastic deformations are observed. On the other hand, among the deformations that a woven reinforcement undergoes during forming, in most cases, only bending is subject to loading/unloading stresses. The first objective of this work is to highlight the inelastic bending behavior of textile reinforcements during a forming process and to find the possible origins of inelasticity. The second objective is to find the cases generating bending loading/unloading during forming as well as to study the influence of the bending inelasticity on forming simulation. For this purpose, the inelastic bending behavior was characterized by three-point bending tests. Then, the Dahl friction model was adapted to bending to describe the inelastic behavior. Finally, this model was implemented in a finite element code based on shell elements allowing the study of the influence of taking into account the inelastic behavior in bending on the numerical simulation of forming.